The Arabidopsis Cysteine-Rich Receptor-Like Kinase CRK36 Regulates Immunity through Interaction with the Cytoplasmic Kinase BIK1 - Lee, Dong Sook; Kim, Young Cheon; Kwon, Sun Jae; Ryu, Choong-Min; Park, Ohkmae K. (Frontiers in Plant Science, 2017)
Receptor-like kinases are important signaling components that regulate a variety of cellular processes. In this study, an Arabidopsis cDNA microarray analysis led to the identification of the cysteine-rich receptor-like kinase CRK36 responsive to the necrotrophic fungal pathogen, Alternaria brassicicola. To determine the function of CRK36 in plant immunity, T-DNA-insertion knockdown (crk36) and overexpressing (CRK36OE) plants were prepared. CRK36OE plants exhibited increased hypersensitive cell death and ROS burst in response to avirulent pathogens. Treatment with a typical pathogen-associated molecular pattern, flg22, markedly induced pattern-triggered immune responses, notably stomatal defense, in CRK36OE plants. The immune responses were weakened in crk36 plants. Protein-protein interaction assays revealed the in vivo association of CRK36, FLS2, and BIK1. CRK36 enhanced flg22-triggered BIK1 phosphorylation, which showed defects with Cys mutations in the DUF26 motifs of CRK36. Disruption of BIK1 and RbohD/RbohF genes further impaired CRK36-mediated stomatal defense. We propose that CRK36, together with BIK1 and NADPH oxidases, may form a positive activation loop that enhances ROS burst and leads to the promotion of stomatal immunity.